MINERALOGY, PETROLOGY AND GEOCHEMISTRY OF BERYLLIUM: AN INTRODUCTION AND LIST OF BERYLLIUM MINERALS - Grew E.S. (My University, 2002)
In 1996, in collaboration with Lawrence Anovitz, I edited Boron Mineralogy, Petrology and Geochemistry , volume 33 in the Reviews in Mineralogy series, a book that has been reprinted with addenda in 2002 (further addenda and corrections are posted at http://www.minsocam.org, where you may also find corrections to this volume). Many of the same reasons for inviting investigators to contribute to a volume on boron apply equally to a volume on beryllium. Like B, Be poses analytical difficulties, and it has been neglected in many geochemical, mineralogical and petrological studies. However, with the development of instruments to measure cosmogenic isotopes, greater availability and refinement of the ion microprobe, and with overall improvement in analytical technology, interest in Be and its cosmogenic isotopes has increased, and more studies are being published. Thus, I decided that it was an appropriate time to invite those actively involved in research on Be to contribute to this volume, which is intended to be a companion to Boron Mineralogy, Petrology and Geochemistry . NOTE: In this chapter, individual review papers are referred to by author name(s) and chapter number. The Be mineral beryl and its colored variants emerald, aquamarine, and “chrysoberyl” (= golden beryl, not the present chrysoberyl) were known to the ancients, and Pliny the Elder had noted that many persons considered emerald and beryl “to be of the same nature” (Sinkankas 1981, p. 20; also Dana 1892; Weeks and Leicester 1968). However, not until 1798 was it realized that beryl contained a previously unknown constituent; analyses before then yielded only silica, alumina, lime and minor iron oxide (Vauquelin 1798; Anonymous 1930; Weeks and Leicester 1968; Greenwood and Earnshaw 1997). The mineralogist Rene Just Hauy asked Nicolas Louis Vauquelin (Fig. 1) to analyze beryl and emerald in order to …